Hotel De Anza. - Gordon, John C. (photographer):::Creator::::::::::::
"This picture was taken at the northwest corner of North Almaden and St. John Streets. The neoclassic building on the left was the College of Notre Dame Science Hall. In 1966 the Hall was demolished so the the city of San Jose could extend Almaden Boulevard northward from Santa Clara Street.